Problematika Dakwah di Kalangan Minoritas Muslim Desa Poka Kota Ambon - Renel, Baiti (Jurnal Komunikasi Islam, 2017)
This paper provides an in-depth analysis of proselytizing problems and strategies among the Muslim minority in Poka Village, Ambon City. Using qualitative des–criptive method, this research concludes that many da'is in Poka village have faced two main problems both internal and external issues. The former related to the number of da'i, the role of da'wah institutions which is not optimal, and the lack of community solidarity in propagating Islam. In addtion, many da’is do not possess a high Islamic intellectual quality and a good quality of education. The latter problems related to the lack of government attention on Islam as well as the dominant influence of non-Muslim environments. While da’wah strategies conducted by da'is are da’wah bi al-lisan and da'wah bi al-hal.